2008
DOI: 10.1183/09031936.00109607
|View full text |Cite
|
Sign up to set email alerts
|

Slow breathing reduces sympathoexcitation in COPD

Abstract: Neurohumoral activation has been shown to be present in hypoxic patients with chronic obstructive pulmonary disease (COPD). The aims of the present study were to investigate whether there is sympathetic activation in COPD patients in the absence of hypoxia and whether slow breathing has an impact on sympathoexcitation and baroreflex sensitivity.Efferent muscle sympathetic nerve activity, blood pressure, cardiac frequency and respiratory movements were continuously measured in 15 COPD patients and 15 healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
138
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(160 citation statements)
references
References 33 publications
(50 reference statements)
11
138
1
10
Order By: Relevance
“…First, while there is strong evidence to suggest that LF R-R interval fluctuations are baroreflex dependent (17), the origin of respiratory-related R-R interval fluctuations is a matter of intense debate, with some arguing for a baroreflex interaction (11,20), whereas others believe that the rhythm is caused by a predominant central mechanism (4,5). This is an important point of contention because existing evidence for an augmented cardiovagal BRS during slow breathing is largely based on the ␣-index calculated at respiratory frequencies (2,21,22); it needs to be acknowledged from the outset that the ␣-index calculated at respiratory frequencies will only provide valid and meaningful results if cardiovascular fluctuations associated with respiration are indeed linked by the baroreflex.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…First, while there is strong evidence to suggest that LF R-R interval fluctuations are baroreflex dependent (17), the origin of respiratory-related R-R interval fluctuations is a matter of intense debate, with some arguing for a baroreflex interaction (11,20), whereas others believe that the rhythm is caused by a predominant central mechanism (4,5). This is an important point of contention because existing evidence for an augmented cardiovagal BRS during slow breathing is largely based on the ␣-index calculated at respiratory frequencies (2,21,22); it needs to be acknowledged from the outset that the ␣-index calculated at respiratory frequencies will only provide valid and meaningful results if cardiovascular fluctuations associated with respiration are indeed linked by the baroreflex.…”
Section: Discussionmentioning
confidence: 90%
“…There is accumulating evidence suggesting that slow breathing in minimally trained individuals is associated with favorable clinical outcomes, such as chemoreflex stabilization in congestive heart failure, sympathetic inhibition in patients with chronic obstructive airway disease, and blood pressure reduction in essential hypertension (2,10,15,22). It has been suggested that the putative augmentation of BRS during slow, deep breathing explains these observations because baroreflex activation inhibits chemoreflex sensitivity (25), which, in turn, may reduce sympathetic tone and lower blood pressure (22). While our data from healthy humans do not disqualify this theory, they point to a possible need to reexamine this hypothesis in patient groups where the slow breathing method of enhancing BRS may have therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a different stimulation of mechanoreceptors rather than an increased chemoreceptor feedback from the working muscle might be involved in the distinct cardiovascular response pattern under low intensity exercise. An alternative or additional explanation for the increase in HRV spectral power and regularity under ISO might be an elevated sensitivity of the baroreflex [77][78][79][80][81]. The shift of the respiration-related HF peak from a higher frequency during DYN to a lower frequency during ISO indicates a reduction of the respiratory rate under ISO.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike in heart failure or hypertension, in patients with diabetes these abnormalities have always been interpreted as evidence of early organic neuropathy [16]. Interestingly, previous studies have shown that a simple functional manoeuvre like slow deep-breathing can increase the BRS [17][18][19], an important and well-established prognostic index, and also reduce the sympathetic tone in conditions like heart failure, hypertension and chronic obstructive pulmonary disease [20][21][22]. In contrast, the upright posture increases sympathetic activity and reduces the BRS [23].…”
Section: Introductionmentioning
confidence: 99%